Defective Cystic Fibrosis Transmembrane Conductance Regulator Accelerates Skeletal Muscle Aging by Impairing Autophagy/Myogenesis - Ziyi Chen; Jiankun Xu; Peijie Hu; Wanting Du; Junjiang Chen; Xiaotian Zhang; Wei Zhou; Jiayang Gao; Yuantao Zhang; Bingyang Dai; Guangshuai Nie; Jun Hu; et al. (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Regenerative capacity of skeletal muscles decreases with age. Deficiency in cystic fibrosis transmembrane conductance regulator (CFTR) is associated with skeletal muscle weakness as well as epithelial cell senescence. However, whether and how CFTR plays a role in skeletal muscle regeneration and aging were unclear. Methods Vastus lateralis biopsy samples from male and female human subjects (n = 23) of 7‐ to 86‐year‐old and gastrocnemii tissues from mice of 4‐ to 29‐month‐old were examined for CFTR expression. Skeletal muscle tissues or cultured myoblasts from mice carrying CFTR mutation (DF508) at 4‐ to 18‐month‐old were used for assessment of muscle mass, contractile force and regenerative capacity as well as myogenic and autophagy signalling. Overexpression of LC3‐β, an autophagy mediator, was conducted to reverse myogenic defects in DF508 myoblasts. Adenoviruses containing CFTR gene or pharmaceuticals that enhance CFTR (VX809) were locally injected into the gastrocnemius or femoris quadricep to rescue age‐related skeletal muscle defects in mice. Results mRNA levels of CFTR in human vastus lateralis exhibited significantly negative correlations with age (r = −0.87 in males and −0.62 in females, p < 0.05). Gastrocnemius mRNA level of CFTR decreased by 77.7 ± 4.6% in 29‐month‐old wild‐type mice compared to the 4‐month‐old. At 18‐month‐old, DF508 mice showed significantly reduced lean mass (by 35.6%), lower specific twitch force of the gastrocnemius (by 46.2%), decrease in fast/slow‐twitch muscle isoform ratio as well as downregulation of myogenic (e.g., MYOD and MYOG) or autophagy/mitophagy (e.g., LC3‐β) genes, compared to age‐matched wild‐types. Post‐injury gastrocnemius regeneration was found impaired in DF508 mice. Myoblast cultures from DF508 mice showed defective myogenic differentiation, which was reversed by overexpressing LC3‐β. In aged (> 15‐month‐old) mice, overexpressing CFTR or VX809 restored the expression of autophagy or myogenic genes, increased mitochondrial LC3‐β level and improved skeletal muscle mass and function. Conclusion Age‐related reduction in skeletal muscle expression of CFTR impairs autophagy and myogenesis, exacerbating skeletal muscle aging. Enhancing CFTR might be a potential treatment strategy for age‐related skeletal muscle disorders.